IMPLEMENTASI PROGRAM ONLINE SINGLE SUBMISSION (OSS) DALAM PELAYANAN PERIZINAN USAHA MIKRO PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN PROBOLINGGO DI ERA NEW NORMAL - Sucahyo, Imam; Adawiyah, Robbiyatul; Mubaroq, Husni (Universitas Panca Marga, 2022)
The purpose of this study was to determine the implementation of the online single submission (OSS) program for micro business licensing services in investment services and one-stop integration services in Probolinggo Regency. This study uses a qualitative method with a descriptive approach. Sources of data used in this study are primary and secondary data. Observation techniques, interviews, and written data collection techniques from the Investment and One-Stop Services Office of Probolinggo Regency. The results of this study indicate that the process of implementing micro business licensing services based on OSS RBA in Probolinggo Regency has been carried out very well. A theory to measure implementation success by Van Meter and Van Horn (Augustino, 2016). This consists of measures/objectives of political policies, resources, characteristics of executors, attitudes (dispositions) of executors, inter-organizational communication and implementation of activities, social, economic and political environmental conditions. The Investment and One-Stop Services Office has made every effort to ensure that the innovation program is carried out as well as possible. However, there are still many business actors who lack knowledge and understanding of service procedures, equipment and infrastructure. As a result, there is a shortage of business entities or MSME players to register their business entities with the OSS.